Lisensi Kreativitas Bersama (Creative Commons License) Dalam Perspektif Hukum Indonesia - Hakim, Dani Amran (Istinbath : Jurnal Hukum, 2021)
The Creative Commons License is the breakthrough that non-profit organizations are making for the internet. Creative Commons has 4 (four) main conditions offered to creators for their copyrighted works, namely Attribution, Non-Comercial, No Derivatives, Share Alike. CCL is a response to the rapid development of internet technology. Various information that is accessed by the public through the internet, not a few of them are intellectual works that are protected by copyright. In the context of today's digital technology, it is very difficult to control activities such as copy-cut-paste (copying-cut-pasting), editing (editing), or sharing of documents (file sharing), which are contradictory to copyright law. So to overcome this, innovation and breakthroughs are needed that allow sharing and using creativity and knowledge without conflicting with legal provisions. The innovation is the Joint Creativity License. Through this license, a person is given the convenience to allow others to reproduce their copyrighted works, provided that their names are still listed. Creative commons is not an alternative to copyright law, but a partner to applicable copyright law.